ANALISIS KADAR AMILOID BETA PLASMA DENGAN GANGGUAN KOGNITIF PADA DIABETES MELITUS TIPE 2 - Yuliarni Syafrita,* Darwin Amir,* Eva Decroli,** Restu Susanti* (Neurona Majalah Kedokteran Neuro Sains, 2017)
INTRODUCTION TYPE 2 DIABETES MELLITUS T2DM AND ALZHEIMERS DISEASE ARE TWO KIND OF NEURODEGENERATIVE DISEASE THAT RELATED WITH AGE PATIENTS WITH DM SHOW A TENDENCY TO DEVELOP ALZHEIMERS DISEASE BUT THERE IS NO SINGLE MARKER FOR PREDICTING A DM CASE WILL DEVELOP INTO ALZHEIMERS DISEASE